Transoral‐transpharyngeal CO2 laser en bloc excision of voluminous left recurrent laryngeal nerve schwannoma: Case report and review of the literature. Issue 12 (30th September 2020) - Mariani, Cinzia; Carta, Filippo; De Seta, Daniele; Nazhmudinov, Ibragim I.; Guseinov, Ismail G.; Magomedova, Kamilla M.; Chuchueva, Natalia; Marrosu, Valeria; Puxeddu, Roberto
Abstract: Recurrent nerve laryngeal schwannoma is a rare benign tumor that, in expert hands, can be treated by transoral CO2 laser surgery. Abstract : Recurrent nerve laryngeal schwannoma is a rare benign tumor that, in expert hands, can be treated by transoral CO2 laser surgery.